Data visualization of blood donation during coronavirus disease (COVID-19) in Perlis / Maisarah Aisisa and Khairul Anwar Sedek - Aisisa, Maisarah; Sedek, Khairul Anwar (College of Computing, Informatics and Media, UiTM Perlis, 2023)
Blood donation is considered as collecting blood for a limited time before use, there is an ongoing need for a steady supply. Healthy individuals must donate blood on a regular basis to ensure that blood is always accessible whenever and wherever it is necessary, especially based on their respective blood types. However, during the COVID-19 pandemic that was expected to have a negative impact on blood system activities and reduce blood supply as an unintended consequence of social distancing measures against blood donation activities. The pandemic Covid-19 causes the percentage rate of blood donors to decrease dramatically. This study helps society to receive the trustworthy source of blood donation activities. Moreover, this study uses data visualization approaches to present blood donation information. This is because of society having a lack of awareness and knowledge to having a blood donation. Therefore, graphical elements will be used in interactive dashboard to improve the user understanding on analyzing the blood donation consequences during Covid-19 pandemic. The dashboard application will assist organisational leaders in accessing information resources in the form of visualisation. The dashboard system's purpose is to deliver basic information of the blood donate, as well as abstract performance measurement and intuitive visualisation. The finding of this research will provide evaluation on presentation of blood donate information among society. The methodology used in the creation of the system is divided into four phases which is preliminary study, analysis, development, and testing. It focuses on explaining problem statements, project objectives, project scope, and project significance at the preliminary study phase.